Three shot burst - DePoy, Phillip (DePoy, Phillip. Foggy Moskowitz series., 2017)
Foggy Moscowitz is called to Mary's Shallow Grave, everyone's favorite bar. A man has been killed--shot three times--by a young girl. With no parents, no fixed abode, and no services to help her, Foggy is forced to shelter her in his beachside apartment. The victim was the son of the richest Seminole in Florida, Ironstone Waters, who sends several of his men, including Mister Redhawk, to collect the girl and find out what happened. With Ironstone's men, a Colombian drug cartel, and the police all in pursuit, Foggy has nowhere to turn but to John Horse. And with some help from the Seminole mystic, Foggy realizes some disturbing truths.